Host genetics and invasive fungal diseases : towards improved diagnosis and therapy? - Cunha, Cristina (2012)
Invasive fungal diseases are life-threatening conditions affecting severely immunocompromised patients such as stem-cell transplant recipients. Recent concerns over antifungal prescription and the exceptionally high healthcare costs owing to the chronic course and high mortality rates of fungal diseases have been shifting the attention from universal antifungal prophylaxis to risk stratification and preemptive approaches [1]. This has motivated the search for ‘individual’ risk factors with prognostic value for the identification of patients most vulnerable to fungal diseases. Therefore, genetic screening strategies are expected to be successfully employed in the near future, to predict risk of disease and efficacy of antifungal therapies.